THE RELATIONSHIP BETWEEN GADGET USE BEHAVIOR AND SLEEP QUALITY - Utomo, Tranggono Yudo; Simamora, Radot Een Romulus; Pariama, Ganda (SYNTIFIC, 2025)
Background. Rapid technological advancements have made gadgets an essential part of students' daily lives. However, excessive gadget use can have negative impacts, particularly on sleep quality. This study aims to investigate the relationship between gadget use behavior and sleep quality among students from the Faculty of Medicine at Universitas Kristen Indonesia (UKI), specifically those in the 2023 class. Research Method. The study employed a cross-sectional design with a quantitative approach, involving 138 university students as a sample collected through a total sampling technique. Data were collected using the SAS-SV (Smartphone Addiction Scale Short Version) questionnaire to measure gadget use behavior and the PSQI (Pittsburgh Sleep Quality Index) to assess sleep quality. Data analysis was performed using the chi-square test with the help of SPSS. Findings. The study's results showed that 84.1% of respondents exhibited negative gadget usage behavior, and 86.2% experienced poor sleep quality. A chi-square test showed a significant relationship between gadget usage behavior and sleep quality (p = 0.000). This study suggests that excessive gadget usage negatively impacts students' sleep quality. Conclusion. Managing gadget use wisely is crucial for improving the quality of sleep and overall health of students.